Обмеження юрисдикційного імунітету РФ щодо шкоди, завданої фізичним та юридичним особам в Україні, унаслідок збройної агресії - Жорнокуй, Ю. М.; Zhornokui, Yu. M.; Жорнокуй Юрій Михайлович (Нове українське право. – 2023. – Вип. 5. – С. 12-18, 2023)
У статті проведено аналіз переваг та недоліків застосування концепцій абсолютного та обмеженого юрисдикційного імунітетів держави в рамках публічних та приватних відносин. Дослідження вказаних різновидів державних імунітетів здійснене у контексті обґрунтування обмеження юрисдикційного імунітету РФ щодо шкоди, завданої фізичним та юридичним особам в Україні внаслідок збройної агресії. Увага акцентована на тому, що держава не має права посилатися на судовий імунітет у справах, пов’язаних із завданням шкоди здоров’ю, життю та майну, якщо така шкода повністю або частково завдана на території держави суду та якщо особа, яка завдала шкоду, у цей час перебувала на території держави суду. Обстоюється думка, що сучасні реалії міжнародного публічного та приватного життя свідчать про тенденції до чіткого обмеження застосування концепції абсолютного імунітету держави виключно межами публічних представницьких відносин (призначенням дипломатичних делегацій, відкриттям консульств тощо).

The author of the article has accomplished analysis of the advantages and disadvantages of implementing the concepts of absolute and limited jurisdictional immunities of the state within the framework of public and private relations. The study of the indicated types of state immunities has been carried out in the context of the legal background of the limitation of the Russian Federation’s jurisdictional immunity in regard to the damage caused to individual persons and legal entities in Ukraine as a result of armed aggression. Particular attention has been focused on the fact that the state does not have the right to invoke judicial immunity in cases related to the damage caused to health, life and property, if such damage is fully or partially caused on the territory of the state, where the court is located and if the person, who caused the damage, was at that moment on the territory of the state, where the court is located. The author argues the opinion that modern realities of international public and private life indicate tendencies to clear limitation of applying the concept of absolute immunity of the state exclusively by the margins of public representative relations (appointment of diplomatic delegations, opening of consulates, etc.). Besides, it has been proved that the state cannot use the concept of absolute immunity within the framework of commercial (trade) and tortious property relations (cause of damage to the life and health of individual persons, as well as to the property of individual persons and legal entities). It has been emphasized that in the context of the Russian Federation’s armed aggression against Ukraine and causing damage to the life and health of individual persons, as well as the property of individual persons and legal entities, the Russian Federation as an aggressor cannot use any state jurisdictional immunity, due to its violation both of the European Convention on State Immunity (1972) and the UN Convention on Jurisdictional Immunities of States and Their Property (2004), and of the fundamental principles and norms of international law, in particular the Convention for the Protection of Human Rights and Fundamental Freedoms and the UN Charter.

Выяснена сущность ограничения юрисдикционного иммунитета РФ в отношении ущерба, причиненного физическим и юридическим лицам в Украине в результате вооруженной агрессии.
Limitation of jurisdictional immunity of the Russian Federation regarding damage caused to individual persons and legal entities in Ukraine as a result of armed aggression
Keywords: імунітет; юрисдикційний імунітет; судовий імунітет; імунітет від попереднього забезпечення позову; імунітет від примусового виконання судового рішення; шкода; відповідальність; фізична особа; юридична особа; immunity; jurisdictional immunity; sovereign immunity; immunity from preliminary injunction; immunity from levying of execution of a judgement; damage; liability; individual person; legal entity; иммунитет; юрисдикционный иммунитет; судебный иммунитет; иммунитет от предварительного обеспечения иска; иммунитет от принудительного исполнения судебного решения; вред; ответственность; физическое лицо; юридическое лицо